Increasing the Provision of Horticultural Seeds in the Women's Farmer Group "Tunas Mekar Sari" Bakas Village, Banjarangkan District, Klungkung, Bali - Yuliartini, Made Sri; Ida Bagus Komang Mahardika; Anak Agung Ngurah Mayun Wirajaya; Anak Agung Sagung Putri Risa Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Agricultural products produced by the people of Bakas Village do not come from farmers who have been struggling with paddy fields, but with the passage of time and a change in the paradigm of the community, agricultural activities have been carried out by women who are members of a forum, namely the " Women's Farmer Group" with their activities in agriculture, namely the provision of horticultural seeds, the use of land owned by groups and yards of houses but has not been managed optimally and continuously. The Community Service (PKM) was carried out in Bakas Village, Banjarangkan District, Klungkung. This applied research aimed to improve the understanding of nursery technology in the women’s farmer group and increase the ability to provide more complete and sustainable horticultural seeds; the correct and appropriate technology of horticultural crop cultivation for the group of women’s farmers is increasing so that the results obtained increase; hydroponically as well as aquaponics (a combination of fishery and vegetable cultivation) for sustainable land use and availability The implementation of service activities to achieve goals includes providing counseling materials, training, field practices, application of technology and assistance. The external targets achieved by the partner farmer women's group can increase the income and welfare of its members through the sustainable manufacture of seeds, the improvement of sustainable food with hydroponic and aquaponic systems as well as the intensive utilization of group-owned land